Pengaruh Harga Dan Kualitas Produk Terhadap Minat Beli Masyarakat Dalam Menggunakan Iconnet Di Kec Lubuk Buaya Kota Padang - Mesi Sefrianti; Dewirahmadanirwati Dewirahmadanirwati (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to analyze the influence of price and product quality on people's buying interest in using iconnet in the district. Padang city crocodile pit. This type of research is quantitative research using a descriptive approach. The total sample of 98 respondents was selected based on the Slovin formula. The data collection technique was carried out by distributing questionnaires to respondents. The collected data was analyzed using multiple linear regression analysis with the help of SPSS statistical software. The results of this research show that the influence of price and product quality has a significant positive effect on people's buying interest in using iconnet in the sub-district, Lubuk crocodile, Padang city.